Integration of ESG, Profitability, and Good Corporate Governance: Strategy for Increasing Firm Value - Azizah, Fatkhiyatul; Setyahuni, Suhita Whini; Yovita, Lenni; Oktavia, Vicky (Indonesia Banking School, 2025)
This study aims to determine the effect of ESG disclosure, profitability, and governance (GCG) on firm value proxied by Tobins’Q. This study falls into the category of quantitative research. A total of 67 non-financial companies listed on the IDX were included in the sample for 2019 to 2023. The sampling method used was purposive sampling. Data analysis was carried out using multiple regression methods. The results showed that ESG, institutional ownership, independent board of commissioners and audit committee have an effect on firm value. While financial performance has no effect on firm value. These findings are deepened by including profitability and governance (GCG) variables, with a concentration on non-financial companies listed on the IDX. The theoretical framework applied includes legitimacy theory and agency theory.